Hypertrophic pyloric stenosis: Early presentation with hyperbilirubinemia - Mishra, Rajeeva; Maji, Prabir (Indian Journal of Child Health, 2014)
Hypertrophic Pyloric Stenosis commonly presents with non-bilious progressive vomiting usually after a feed. The vomiting usually starts after third week with a range of symptoms onset from first week to fifth month of life. Less commonly it is associated with hyperbilirubinemia (unconjugated > conjugated) which subsides after surgical correction. We report a case of Hypertrophic Pyloric Stenosis who presented early in fifth day of life with repeated vomiting after each feed and unconjugated hyperbilirubinemia. Ultrasonography revealed Hypertrophic Pyloric Stenosis without any evidence of other cause of jaundice. Patient was treated conservatively, prepared for surgery, surgical correction done with Ramstedt’s Pyloromyotomy following that vomiting and jaundice both subsided. Early presentation of HPS may suggest congenital etiology and association of unconjugated hyperbilirubinemia should alert clinician for future Gilbert Syndrome.